EFFECT OF RENAL DENERVATION ON RENAL FUNCTION OF PATIENTS WITH UNCONTROLLED HYPERTENSION: INSIGHTS FROM A SYSTEMATIC REVIEW AND META-ANALYSIS OF RANDOMIZED, SHAM-CONTROLLED TRIALS. (April 2021) - Stavropoulos, Konstantinos; Katsimardou, Alexandra; Patoulias, Dimitrios; Imprialos, Konstantinos; Bouloukou, Sofia; Tegou, Zoi; Bakaloudi, Dimitra; Kerpiniotis, Georgios; Dimitriadis, Kyriakos; Papademetriou, Vassilios; Tsioufis, Konstantinos; Doumas, Michael
Abstract : Objective: Renal denervation (RDN) has been studied extensively during the last decade. Its role in the management of resistant hypertension has been placed at the epicenter. Its effect on renal function however represents a major safety issue. Design and method: PubMed and CENTRAL, along with grey literature sources, were searched from their inception to May 2019 for randomized, sham-controlled trials primarily evaluating the efficacy and safety of RDN on the management of hypertension, irrespective of study blinding, setting and sample size. We extracted those data concerning the effect of RDN on renal function of enrolled participants. Results: Six randomized, sham-controlled trials were identified and included in the meta-analysis. In total, 981 patients with hypertension were randomized in all 6 trials to undergo either RDN (n = 585) or sham-procedure (n = 396). RDN was associated with a non-significant decrease in estimated glomerular filtration rate by 0.24 ml/min/1.73 m2 (95% CI: -1.95 to 1.47; I2 = 0%), compared to sham procedure. It was also observed that restriction of the analysis on second-generation trials did not alter significantly the observed effect estimate (mean difference = -0.02; 95% CI: -2.64 to 2.62; I^2 = 0%). Finally, no difference was detected in serum creatinine levels, when RDN was compared to sham (mean difference = 0.00; 95% CI: -0.02 to 0.02; I^2 = 0%). Conclusions: RDN constitutes a safe procedure, as far as renal function is concerned. It has to be admitted however, that all trials were relatively short-term (up to 1 year); thus, data from long-term studies are needed to confirm the renal safety of RDN.